2012
DOI: 10.1007/s00404-012-2501-5
|View full text |Cite
|
Sign up to set email alerts
|

First-trimester serum folate levels and subsequent risk of abortion and preterm birth among Japanese women with singleton pregnancies

Abstract: Objectives: To determine whether a low serum folate level during the first trimester predicts subsequent late abortion, preterm birth, or fetal growth restriction (FGR). Study design:A prospective cohort study involving 5,075 women whose serum folate levels were measured during the first trimester. The participants were informed of their serum folate levels. Results:The pregnancy duration, birthweight, rate of late abortion/preterm birth, and the rate of FGR did not differ significantly among four groups class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…In nonpregnant adults, exposure to smoking is negatively associated with folate and (Yamada et al, ) vitamin B12 levels and positively associated with homocysteine levels (Mannino, Mulinare, Ford, & Schwartz, ; O'Callaghan, Meleady, Fitzgerald, & Graham, ). A number of studies have examined this association in pregnant women, but a complete overview of published literature is currently not available (Bakker, Timmermans, Steegers, Hofman, & Jaddoe, ; Bergen et al, ; Nilsen et al, ; Relton, Pearce, & Parker, ; Yamada et al, ). Therefore, we aimed to systematically review the literature evaluating the associations of exposure to smoking during pregnancy with levels of folate, vitamin B12, and homocysteine in maternal and cord blood.…”
Section: Introductionmentioning
confidence: 99%
“…In nonpregnant adults, exposure to smoking is negatively associated with folate and (Yamada et al, ) vitamin B12 levels and positively associated with homocysteine levels (Mannino, Mulinare, Ford, & Schwartz, ; O'Callaghan, Meleady, Fitzgerald, & Graham, ). A number of studies have examined this association in pregnant women, but a complete overview of published literature is currently not available (Bakker, Timmermans, Steegers, Hofman, & Jaddoe, ; Bergen et al, ; Nilsen et al, ; Relton, Pearce, & Parker, ; Yamada et al, ). Therefore, we aimed to systematically review the literature evaluating the associations of exposure to smoking during pregnancy with levels of folate, vitamin B12, and homocysteine in maternal and cord blood.…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies have suggested that a higher level of folate in pregnancy is associated with higher birth weight, increased placental weight and fewer preterm births [28,55-57], although these results have not been confirmed in other populations recently [58]. At present the association between folate insufficiency and the onset of placenta-mediated diseases, such as spontaneous abortion [58-65], preterm birth [66-75], foetal growth retardation [76-80], pre-eclampsia [81-88], abruptio placentae [89] and stillbirth [90] is still not entirely clear.…”
Section: Introductionmentioning
confidence: 99%
“…At present the association between folate insufficiency and the onset of placenta-mediated diseases, such as spontaneous abortion [58-65], preterm birth [66-75], foetal growth retardation [76-80], pre-eclampsia [81-88], abruptio placentae [89] and stillbirth [90] is still not entirely clear.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 In addition, 5-MTHF was observed to be an equally effective alternative to folic acid in decreasing total homocysteine concentrations(tHcy)in women. 15 Daily use of 400 μg folic acid per day has been recommended by public health authorities worldwide before and during early week of gestation to reduce the risk of NTDs. 4,5 Despite proven efficacy, the use of iron and folic acid (IFA) supplements during pregnancy is low with only 38% of women reporting regular intake during their last pregnancy.…”
Section: Discussionmentioning
confidence: 99%